A atuação profissional em políticas públicas de esporte e lazer: saberes e competências - Bruno Ocelli Ungheri (2014)
Sport and leisure are social rights guaranteed by the Brazilian Constitution of 1988. Therefore, public policies developed by the governments should focus on the promotion of and the access to sport and leisure for the public. The perception of the professionals who develop these public policies is relevant to understand the competencies, skills, and knowledge necessary for a consistent professional performance withthe objectives of the proposed policy. This study analyzes the profiles of the professionals who, in different degrees, manage public policies for sportleisure in the Municipal Secretaryof Sports and Leisure in Belo Horizonte (SMEL). The organization is responsible for the development of projects and programs that aim to ensure sport and leisures social rights of the population residing in this county; furthermore, management of equipment, infrastructure, and events are also included within its responsibilities. For this study, I used a qualitative approach involving literature review and field research. For the development of the literature review, I analyzed books and periodicals that addressed politics, public policies, and the possibilities of its development with regards to sport and leisure, and references on training and activities of the professionals involved in this route. The field research took place in two different stages; the first stage was an immersion in the field of study. The second phase involved the completion of nine semi-structured interviews with eight analysts and one manager. The first stage allowed me to observe the everyday relationships established at SMEL, as well as toknow its programs and professionals responsible for its development. Phase two involving interviews revealed the respondent’s perceptions about their professional practice, focusing on the formation process, their responsibilities, the particularities of their daily lives, and their frustrations. Through the proposed analysis, I realized that there are two paths complementary to professional performance with in the public policies of sport and leisure. The first refers to the initial (or formal) training of the subjects, when they are presented with the specific contents of the area of activity they choose. Unfortunately this comes with little or no in depth knowledge related to public policy. Formal training is complemented with practice, in other words, with the entrance of the professionals into the labor market. Thus, the difficulties and problems experienced in the field allow professionals to identify gaps in their training, which in the context analyzed, are primarily related to the lack of knowledge as sociated with management. Therefore, analysts act as managers of each program developed in the SMEL, being directly responsible for financial control, performance of the work teams, strategic planning of actions, and relationships with the community without proper management education. In this study, we note that the professional’s profile to act in public policies of sport and leisure is composed of a triad that involves specific knowledge of the area of expertise, knowledge about politics, and finally, domain of the main contents related to management.